Resolver Models for Manufacturing - Figueiredo, Joao (2012)
This paper develops a new mathematical model, for Pancake resolvers, dependent on a set of variables controlled by a resolver manufacturer – the winding parameters. This model allows a resolver manufacturer to manipulate certain in-process controllable variables in order to readjust already assembled resolvers that without any action would be scrap for the production line. The developed model follows a two-step strategy where on a first step a traditional transformer’s model computes the resolver nominal conditions and on a second step a linear model computes the corrections on the controllable variables, in order to compensate small deviations in design assumptions, caused by the variability of the manufacturing process. An experimental methodology for parameter identification is presented. The linearized model develops a complete new approach to simulate the product characteristics of a Pancake Resolver from the knownledge of manufacturer controllable variables (winding parameters). This model had been simulated and experimentally tested in a resolver manufacturing plant. The performed tests prove the efficiency of the developed model stabilizing the product specifications in a dynamic environment with high variability of the production processes. All experiments had been led at the resolver manufacturer Tyco Electronics – Plant Evora